Sustaining sanitation and hygiene behaviours - Beenakumari Govindan; Rebecca E. Scott (2003)
The two projects examined in this paper assume historical relevance in so far as Pilicode was initiated prior to the Peoples’ Planning Movement, while Alappad began well into the movement. Pilicode contributed to developing models during the movement, while Alappad was designed by drawing on lessons from Pilicode. The two projects, with their differences and commonalities in success and failure, offer lessons for formulating such projects elsewhere.